Formulasi dan Evaluasi Sediaan Sabun Cair dari Umbi Porang (Amorphophallus muelleri Blume): - Novia Agustini Irmasyari Siregar; Roy Indrianto Bangar; Erida Novriani (Yayasan Literasi Sains Indonesia, 2026)
Porang tuber (Amorphophallus muelleri Blume) is a potential natural resource that can be developed as an active ingredient in cosmetic preparations, particularly liquid soap. This study aimed to formulate and evaluate liquid soap containing porang tuber extract and to determine its physical quality characteristics. The tubers were extracted by maceration using 70% ethanol. Prior to extraction, simplicia characterization was performed, including determination of moisture content, water-soluble extractive, ethanol-soluble extractive, total ash, and acid-insoluble ash. Phytochemical screening was carried out to identify secondary metabolites. The extract was formulated into liquid soap preparations with concentrations of 3%, 5%, and 8%. The evaluation included organoleptic tests, pH measurement, foam height test, irritation test, and hedonic test. The results of simplicia characterization showed that all parameters met the requirements of the Herbal Pharmacopeia. Phytochemical screening indicated the presence of alkaloids, flavonoids, saponins, tannins, and triterpenoids. The formulated liquid soaps showed acceptable physical characteristics, pH values within the Indonesian National Standard range (8–11), adequate foam formation, and no skin irritation. Hedonic testing demonstrated that all formulations were acceptable to panelists. It can be concluded that porang tuber extract has potential as a natural active ingredient in liquid soap formulations.